A method of analysis of spontaneous electromagnetic emission of the Earth: physical backgrounds, elements of theory, field experiment - V.N. Shuman; V. P. Kobolev; V. I. Starostenko; I. B. Burkinskiy; N. P. Loyko; I. G. Zakharov; D. A. Yatsiuta (Геофизический журнал, 2012)
Existing and new approaches to the analysis of spontaneous electromagnetic emission generated by the lithosphere in the wide frequency range outlined lately have been analyzed in the article. Considerations of a set of problems and controversial topics of its generation and propagation and some results of field experiments permitted to accentuate the commonness and differences of methods of natural impulse electromagnetic field of the Earth measurements and analysis of spontaneous electromagnetic emission of the Earth, to outline the contours and perspectives of their practical application.